HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA TENTANG JERAWAT DI SMP ADVENT PARONGPONG - Evi Martha Suryani; Imanuel Sri Mei Wulandari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
ABSTRACT Introduction: Acne vulgaris is a chronic inflammation of the pilosebaceous unit with clinically polymorphic lesions consisting of non-inflammatory (open and closed, comedones) and inflammatory lesions (papules, pustules, and nodules) with varying degrees of inflammation. Several factors can cause negative feelings or mental health problems due to acne, such as reduced self-esteem and self-confidence, shyness, avoiding direct contact with people, feelings of helplessness, anxiety, and fear. The incidence or cases of acne The increasing number can be caused by many factors, one of which and the most important is the level of knowledge and how to respond to it. Objective: to determine the level of knowledge and attitudes of adolescents about acne. Methods: this study uses a quantitative design with aapproach cross sectional. Sampling used total sampling with a total of 58 respondents. This research was conducted at the Parongpong Adventist Middle School. Conclusion: the results of the research test showed that the level of knowledge of Parongpong Junior High School students about Acne was moderately knowledgeable with a percentage value (77.6%), while the Parongpong Junior High School students' attitudes about Acne were having a negative attitude with a percentage value (53.4 %). The results of the statistical test analysis using Spearman Rho with the level of closeness of relationship = 0.486 (<0.5), and has a p-value of0.000 (p<0.05). These results indicate that there is a significant relationship between knowledge and attitudes of Parongpong Junior High School students about acne. Suggestion: It is necessary to increase knowledge about acne, especially in adolescents. The researcher hopes that the school can work together with health workers to carry out socialization and counseling about acne. It is hoped that further researchers will conduct research on acne with different variables.